Divergent evolution drives high diversity of toll-like receptors (TLRs) in passerine birds: Buntings and finches. (July 2023) - Włodarczyk, Radosław; Těšický, Martin; Vinkler, Michal; Novotný, Marian; Remisiewicz, Magdalena; Janiszewski, Tomasz; Minias, Piotr
Abstract: Toll-like receptors (TLRs) form a key component of animal innate immunity, being responsible for recognition of conserved microbial structures. As such, TLRs may be subject to diversifying and balancing selection, which maintains allelic variation both within and between populations. However, most research on TLRs in non-model avian species is focused on bottlenecked populations with depleted genetic variation. Here, we assessed variation at the extracellular domains of three TLR genes ( TLR1LA, TLR3, TLR4 ) across eleven species from two passerine families of buntings (Emberizidae) and finches (Fringillidae), all having large breeding population sizes (millions of individuals). We found extraordinary TLR polymorphism in our study taxa, with >100 alleles detected at TLR1LA and TLR4 across species and high haplotype diversity (>0.75) in several species. Despite recent species divergence, no nucleotide allelic variants were shared between species, suggesting rapid TLR evolution. Higher variation at TLR1LA and TLR4 than TLR3 was associated with a stronger signal of diversifying selection, as measured with nucleotide substitutions rates and the number of positively selected sites (PSS). Structural protein modelling of TLRs showed that some PSS detected within TLR1LA and TLR4 were previously recognized as functionally important sites or were located in their proximity, possibly affecting ligand recognition. Furthermore, we identified PSS responsible for major surface electrostatic charge clustering, which may indicate their adaptive importance. Our study provides compelling evidence for the divergent evolution of TLR genes in buntings and finches and indicates that high TLR variation may be adaptively maintained via diversifying selection acting on functional ligand binding sites. Highlights: Toll-like receptors (TLRs) may show high levels of polymorphism in wild bird populations. Positively selected sites within TLRs are functionally important and can influence their ligand-binding properties. TLR variation may be adaptively maintained via diversifying selection acting across closely-related species.